(untitled) (Journal of Libya for geographical studies, 2022)
Depending on the availability of land cover and land use (LCLU) data and their importance in studying the impacting changes in environmental and climatic systems, and as these data provide opportunities to increase scientific research in the environmental field at the landscape level. Reports of accuracy for this data can be high and acceptable, but at the same time they are untrue and misleading. From this point of view, one of the first concerns of the remote sensing community has become to improve the quality of data and the methodology for extracting land cover information and land uses, in addition to the advantages provided by satellite methodologies, there are limitations that must be realistically measured to be made clear to users of this data so that they can make correct decisions about it and the possibility of its use. Accuracy assessment of these products is the procedure used to measure the quality of these products. Using remote sensing techniques to detect the changes during the period 1988 till 2000 using Landsat TM5 dates (1988, 1992, 1996, and 2000). Also using the different kind of maps which integrated with the remote sensing data to find the relationship between the changes in the land cover in the study area, west of Tripoli at Lon (12: 33:18 -13:21:47) and Lat (32:55:10 - 32:35:44). Supervisor classification carried out using Maximum likelihood method chosen to classify the images. High resolution data such as Quick Bird (2002) and Spot 5 (2000) have been used as reference to choose the training sets and to apply the accuracy assessment for the classification results. The accuracy assessment has been applied was between 67% and 76%, obtained by using the high-resolution data as reference.